From ingest to egress: a green journey - Partridge, J (2020)
If you have purchased a book online recently you'll be aware that your delivery commonly arrives bubble-wrapped, padded with extra 'crumpled' paper, stuffed in a cardboard box, with invoice (and advertisements), sealed and secured with plastic strapping - no small amount of material for a relatively small item. The Bodleian Libraries Acquisitions team receives thousands of new purchased material like this through library doors each month. As such those teams have decided to take action to reduce the impact of the packaging being received. So what does the journey of a purchased book, and its packaging, look like in the Libraries?